Information and Communication Technology (ICT) in the learning process among students of University Utara Malaysia: Education IR 4.0 - Aziz, Nor Umirah; Mustafar, Mastora (Universiti Utara Malaysia, 2020)
Information and Communication Technology (ICT) plays an important role in teaching and learning in the 21st century. Recognizing this fact, the Ministry of Higher Education Malaysia (KPTM) has taken the 9th step in online learning globally as a step towards leading the education system in line with developed countries. Therefore, this study was conducted to study the level of students using ICT in the learning process as well as to study the level of ICT in learning methods in UUM. The sample of this study was 109 students in UUM. The data were collected using questionnaires and analyzed using Statistical Package for Social Sciences (SPSS) 25. Results from the descriptive analysis indicate that the level of readiness of students to use ICT in the learning process is high. In addition to that, the level of Information and Communication Technology (ICT) usage in the learning method at UUM is also high. The results of this study are expected to provide important information to the University Utara Malaysia (UUM) and its students in an effort to increase the level of readiness and use of ICT in teaching and learning in UUM in general. Finally, this study will also be a starting point for other researchers who may wish to conduct further research on this topic in the future in terms of expanding the scope of studies that should include aspects such as level of ICT facilities and facilities in UUM and factors affecting the level of ICT use in UUM.